Perancangan Aplikasi Manajemen Surat Keluar Responsive Dengan Bootstrap Berbasis Web - Aditya Ramadhani; Andrean Akbar Permana; Azlam Abi Yansah; Affan Setya Fahriza; Hendry (Bulletin of Computer Science Research, 2024)
The objective of this project is to develop a Responsive Outgoing Mail Management Application utilizing Bootstrap for the Household and Bappeda Division of Medan City. The objective is to enhance productivity by efficiently gathering, analyzing, and utilizing data inside a commercial entity. Furthermore, he incorporates the assessment and development of a web-based archive management information system for handling incoming and outgoing mail at the Jambi DPRD City Secretariat. The system employs Unified Modeling Language (UML) for the purpose of system modeling. Furthermore, this study highlights the significance of establishing a comprehensive archive system for both incoming and departing emails. The system will be implemented utilizing the Model View Controller (MVC) paradigm, renowned for its efficacy in structuring and overseeing documents throughout the business. The term to summarize, the suggested application for overseeing outgoing mail in the Household Division and Bappeda Medan City aligns with prior research on enhancing effectiveness through web-based systems in various organizational settings. By combining UML modeling and MVC approaches, it is possible to develop apps that effectively streamline outgoing email processes. This research enhances the field of information management systems by offering valuable insights into the development of responsive web apps customized to fit the specific needs of enterprises. This subsequently enhances operational efficiency and optimizes data management processes.